Features of Industrial Production of Penicillin: From Laboratory Discovery to Biotechnological Production - D.Kh. Otanazarov; Sh. U. Norimov; Sultanova Sh.Y; Qalandarov D. Y (American Journal of Biomedicine and Pharmacy, 2026)
Penicillin is the first antibiotic introduced into broad clinical practice, the history of which became the starting point of the era of antimicrobial chemotherapy. However, the path from Alexander Fleming’s accidental observation to the powerful industry of fermentation production took more than a decade and required solving extremely complex biochemical, technological, and engineering problems. This work examines the key features of penicillin biosynthesis, the stages of selection of productive Penicillium chrysogenum strains, the parameters of deep cultivation, and the principal scheme for obtaining semi-synthetic analogues of natural antibiotics. Special attention has been paid to the role of the penicillinase enzyme in the formation of 6-aminopenicillinic acid - a universal "building block" for modern modified penicillins.